Supply Chain Risk Management of Molded Palm Sugar at Besan Village, Dawan District, Klungkung Regency, Bali Province, Indonesia - Arilaksmi, I Gusti Agung Ayu Putu Sri Siwi; Ambarawati, I Gusti Agung Ayu; Dewi, Ni Luh Prima Kemala (Advances in Social Sciences Research Journal, 2026)
The molded palm sugar processing business at Besan Village, Dawan District, Klungkung Regency in Bali, plays an important role in contributing to community’s income. However, the sustainability of this business faces various risks along the supply chain, ranging from unstable palm sap supply to distribution and product quality issues. This study aims to identify actors and to analyze their level of risks, and to formulate appropriate risk mitigation strategies along the molded palm sugar at Besan village. The research involved actors in the molded palm sugar supply chain, including tappers, palm sugar producers, collectors, and retailers. Supply chain process mapping was conducted using the Supply Chain Operations Reference (SCOR) approach. Risk identification and assessment were conducted using the Failure Mode and Effects Analysis (FMEA) method. Finally, prioritization of risk mitigation strategies was analyzed by using the Analytical Hierarchy Process (AHP) method. The results of the study indicate that the risks of the molded palm sugar supply chain are spreading across all supply chain actors. Critical risks are primarily related to the instability of the sap supply in the plan and source processes, as well as the risk of damage and product quality degradation during delivery and return processes. FMEA mapping shows that risks in the red and yellow zones are spread throughout the supply chain, accordingly it requires coordinated risk management. The AHP results indicate that priority risk mitigation strategies include mechanization of climbing equipment, strengthening partnerships, implementing a quality-based pricing system, and increasing the number of business partners. Based on the research results, it can be concluded that risk management in the molded palm sugar supply chain requires a comprehensive and integrated approach across actors. It is recommended that stakeholders and related stakeholders prioritize mitigation strategies that focus on strengthening upstream aspects without neglecting risk control at the downstream stages of the supply chain.